Rainfall Runoff and Dissolved Pollutant Transport Processes Over Idealized Urban Catchments - Zhang, Taotao; Xiao, Yang; Liang, Dongfang; Tang, Hongwu; Yuan, Saiyu; Luan, Bin (Frontiers in Earth Science, 2020)
Urban stormwater runoff is often considered as one of the most significant contributors to water pollution. Particulates are commonly regarded as the primary form of pollutant transport in the urban environment, but the contribution from the dissolved pollutants can also be significant. This study aims to investigate the dissolved pollutant transport process over urban catchments, especially the effects of buildings and spatial distribution of pollutants. The concept of “exchange layer” has been adopted and an equation has been proposed to describe the release process of dissolved pollutant from the exchange layer to the runoff water. A horizontal two-dimensional water flow and pollutant transport model has been developed for predicting dissolved pollutant runoff based on the shallow water assumptions and the advection-diffusion equation. A series of laboratory experiments have been conducted to verify the proposed model. It has been demonstrated that both the rainfall runoff and the pollutant runoff can be predicted accurately. Buildings slow down the runoff and pollutant transport processes, especially when buildings are staggered. The non-uniform distribution of pollutants over the catchment greatly influences the pollutant transport process over the catchment. This work provides insight into the effects of buildings and initial pollutant distribution on the dissolved pollutant transport phenomenon, which can help better design the pollution mitigation strategies.